1962
DOI: 10.1130/0016-7606(1962)73[1431:fsotto]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Flume Studies of the Transport of Pebbles and Cobbles on a Sand Bed

Abstract: During experi ments on sf:d mcnt trnn.sport and real tanca to now with a un.Uorm o. 33 m.r.a sand, data w r t aken on Ute movement ot indh'i• dual rocks having lntermodiato diameters from about O. t to o. 5 foot. Th experiments were conducted in flumo z-toot wide by 60-foet long and for most runs, depth. WM held constant at o. 5 f'eet. The exp r:l menta showed t at rocks on U1e &and bed inov d down tren consistently only it the flow wa.s la the uppor regimci that la, only if 1be ed formi, were plmio boo, stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 0 publications
0
30
1
Order By: Relevance
“…This conclusion contradicts results from flume experiments (e.g. Fahnestock and Haushild, 1962) which indicated that the particles move during the upper regime only.…”
Section: Discussion and Summarycontrasting
confidence: 68%
See 2 more Smart Citations
“…This conclusion contradicts results from flume experiments (e.g. Fahnestock and Haushild, 1962) which indicated that the particles move during the upper regime only.…”
Section: Discussion and Summarycontrasting
confidence: 68%
“…Flume experiments (e.g. Fahnestock and Haushild, 1962;Simons and Senturk, 1992) showed that gravels on sandbed rivers are likely to be embedded and buried by advancing sediment. Here the relation between burial depth and particle size was examined using available data and reported on the basis of the overall seasonal distributions.…”
Section: Burial Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, experimental studies indicate that movement of pebbles and cobbles in sand-bed rivers occurs mainly in the upper reaches where high-velocity flow during flood stage is sufficient to initiate movement. Downstream reaches of sand-bed rivers thus contain fewer pebbles and cobbles (Fahnestock and Haushild, 1962).…”
Section: Geomorphological and Hydrologic Factorsmentioning
confidence: 99%
“…An interesting investigation of the movement of round (almost spherical) rocks in stream flows was found (Fahnestock and Haushild, 1962). Though it lacked details and had limited application to the present problem, it may provide useful information for future investigations of cylinder motion on a sand bed.…”
Section: Background*mentioning
confidence: 99%